Nanocomposites with Liquid-Like Multiwalled Carbon Nanotubes Dispersed in Epoxy Resin without Solvent Process. (11th June 2014) - Zhang, Xi; Zheng, Ya-Ping; Yang, Rui-Lu; Yang, Hai-Cheng
Abstract : Liquid-like multiwall carbon nanotubes (MWNTs) were prepared with as-received carboxylic MWNTs-COOH and poly(ethylene oxide)-block-poly(propylene oxide)-block-poly(ethylene oxide) (PEO-b-PPO-b-PEO) through hydrogen bonding. The sample has liquid-like behavior above 58°C. The MWNTs content is 26.6 wt%. The liquid-like MWNTs nanofluids were incorporated into epoxy matrix with solvent-free process and dispersed well. When the liquid-like MWNTs nanofluids content is up to 1 wt%, the impact toughness of the nanocomposite is 153% higher than the pure epoxy matrix.